2023
DOI: 10.1063/5.0146806
|View full text |Cite
|
Sign up to set email alerts
|

Two-stream instability with a growth rate insensitive to collisions in a dissipative plasma jet

Abstract: The two-stream instability (Buneman instability) is traditionally derived as a collisionless instability with the presumption that collisions inhibit this instability. We show here via a combination of a collisional two-fluid model and associated experimental observations made in the Caltech plasma jet experiment, that in fact, a low-frequency mode of the two-stream instability is indifferent to collisions. Despite the collision frequency greatly exceeding the growth rate of the instability, the instability ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Hao et al 32 showed that as the background plasma density increases, a current-driven instability is first attenuated and then enhanced by collisions, but the two-stream instability (TSI) is always damped by collisions. However, with a two-fluid collisional theory, Zhou and Bellan 33 recently found that in some situations, the TSI cannot be mitigated by collisions even if the collision frequency is larger than the growth rate of the instability.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al 32 showed that as the background plasma density increases, a current-driven instability is first attenuated and then enhanced by collisions, but the two-stream instability (TSI) is always damped by collisions. However, with a two-fluid collisional theory, Zhou and Bellan 33 recently found that in some situations, the TSI cannot be mitigated by collisions even if the collision frequency is larger than the growth rate of the instability.…”
Section: Introductionmentioning
confidence: 99%